DAMAGE LEVEL AND CLAIMED VALUE ESTIMATION OF DAMAGE MANGROVE ECOSYSTEM IN BINTAN BAY, BINTAN DISTRICT - Sigit Winarno; Hefni Effendi; Ario Damar (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
ABSTRACTMangrove ecosystem in some regions of the Bintan Bay has suffered damage due to development of human settlements, developing of land transport infrastructure, and also logging by the community. The aim of this study was to assess the level of damage, factors affecting the damage, and to calculate the estimated value of claims for damaged mangrove ecosystem in the Bintan Bay, Bintan District. The results showed that mangrove vegetation in Bintan Bay consists of 16 species. Based on the analysis of standard criteria and guidelines for mangrove destruction KEPMENLH 201, 2004, the quality of mangroves in Bintan Bay was considered in a good criteria (very dense and medium) and damaged criteria (rare). The observation of satellite images from 1990 to 2013 showed that mangrove area decreased by 501.39 hectares or 27.1%. Contributing factor due to the decrease of mangrove trees was to fuel the manufacture of charcoal, construction of infrastructures such as roads, ports of fishing boats and also the establishment of the fish pond. Based on rehabilitation application scenario for 15 years, the total area of compensated mangrove due to its damage was 1091.727 hectares with rehabilitation cost of about Rp 30.372.391.000,00. Meanwhile, for 30 years scenario rehabilitation, the total damage mangrove area that should be compensated was 1743.406 hectares. Keywords : Bintan Bay, mangrove ecosystem, estimated value damage claims